First case of Primary Progressive Multiple Sclerosis treated with Ocrelizumab in Peru - Cortez-Escalante, Jaqueline (2023)
Multiple Sclerosis is a chronic, demyelinating, autoimmune, neuroinflammatory disease. Known as the most common cause of non-traumatic neurological disability in young adults. Ten per cent of patients with Multiple Sclerosis are diagnosed with the Primary Progressive form (PPMS) which, until the emergence of the anti-CD20 monoclonalantibody Ocrelizumab, had no specific therapy. The first case treated with Ocrelizumab in the Peruvian publichealthcare system is reported. The patient presented an acceptable tolerability and an adequate clinical response, as measured by the EDSS scale. Of note, under Peruvian legislation, Multiple Sclerosis is considered a rare diseaseand, therefore, requires an ad hoc evaluation for the authorization of public funding for specific therapies.